Implementation of the Balanced Scorecard in Higher Education Performance Management: A Comparative Study Between Indonesia and International Cases - Muda, Florianus Pruda (Faculty of Economics and Business, Universitas Klabat, 2026)
Global higher education institutions (HEIs) face complex demands for strategic adaptation. However, the integration of Balanced Scorecard (BSC) perspectives-particularly learning, growth, stakeholder engagement, and sustainability-remains limited in Indonesian HEIs, creating a need for a multidimensional performance framework. Methods: This study analyzes BSC implementation in universities through a comparative analysis of Indonesian and international cases, identifying success factors and challenges. The method used is a Systematic Literature Review (SLR) with thematic analysis of 22 articles from four major academic databases. Findings: Indonesian HEIs tend to focus on financial and internal process indicators. In contrast, international institutions are broader in integrating stakeholder and sustainability dimensions. Key challenges in Indonesia include limited IT infrastructure, academic cultural resistance, and inadequate contextualization of indicators. Success depends on strategic leadership, stakeholder engagement, digital infrastructure, and continuous adaptation. Implications: This study proposes a holistic, context-sensitive, and measurable BSC adaptation model for Indonesian higher education. This research offers practical guidance and a theoretical framework for performance management in HEIs, particularly in developing countries.